The EFFECT OF Anti-miRNA 144 AND Anti-miRNA 150 ON THE EXPRESSION OF α GLOBIN CHAINS IN PBMC - Rini Riyanti (Journal of Stem Cell Research and Tissue Engineering, 2022)
The excess of unbound α globin chains are the basic pathophysiology of the cause of clinical symptoms in major β thalassemia. Recently there are many alternative therapies by increasing γ globin chains to reduced the effects of unbound α globin chains. Alternative therapies by decreasing α globin chains have not been much noticed. α globin expression involves complex regulatory involving transcription factors and miRNAs. It involves GATA-1, KLFD and MYB transcription factors . It also involves miRNA-144 and miRNA-150. The role of miRNA-144 and miRNA-150 to reduce the α globin chains expression in major β thalassemia patients is an alternative therapy. miRNA-144 and miRNA150 activity need to be known by using anti-miRNA 144 and anti- miRNA 150. Analyzed the effect of anti-miRNA 144 and anti-miRNA 150 on the expression of α globin chains. This study was an experimental study using PBMC of a major β thalassemia patients. PBMC divided into four groups that were not transfected, transfected by anti-miRNA 144, transfected by anti-miRNA 150 and transfected by anti-miRNA 144 and anti-miRNA 150. qPCR examinations to find out expression of miRNA-144 and miRNA-150. Western blot examination to find out the expression of α globin chains. There was significantly lower miRNA-144 expression in PBMC of major β thalassemia patients who had been transfected by anti-miRNA 144 than those not transfected. In line with the result of miRNA-144 expression which was 0.17 times lower than the control group. There was significantly lower miRNA-150 expression in PBMC of major β thalassemia patients who had been transfected by anti-miRNA 150 than those not transfected. In line with the result of miRNA-150 expression which was 0.30 times lower than the control group. There was significantly lower α globin chains expression in PBMC thalassemia patients who had been transfected by anti-miRNA 150 than those not transfected. There was significantly lower α globin chains expression in PBMC thalassemia patients who had been transfected by anti-miRNA 150 and anti-miRNA 144 than those not transfected. This is evidenced by the decreased in the area 10-25 KDa band. Based on this study, the administration of anti-miRNA 150 or anti-miRNA 144 and anti-miRNA 150 is capable of decreasing the expression α globin chains in PBMC of major β thalassemia patients.